Hybrid Planning and Hierarchical Optimization of Mechatronic Systems - Münch, Eckehard; Adelt, Philipp; Krüger, Martin; Kleinjohann, Bernd; Trächtler, Ansgar (Proceedings of the International Conference on Control, Automation and Systems (ICCAS))

Development and Control of a Quarter-Vehicle Testbed for a Fully Active X-by-Wire Demonstrator - Nachtigal, Vitalij; Jäker, Karl-Peter; Trächtler, Ansgar (9th International Symposium on Advanced Vehicle Control (AVEC 2008))

Organization and Control of Autonomous Railway Convoys - Henke, Christian; Tichy, Matthias; Schneider, Tobias; Böcker, Joachim; Schäfer, Wilhelm (Proceedings of the 9th International Symposium on Advanced Vehicle Control, Kobe, Japan)

Self-optimization of an Active Suspension System Regarding Energy Requirements - Voecking, Henner; Trächtler, Ansgar (International Conference on Control, Automation and Systems 2008 (ICCAS))

Mechatronic Design and Implementation of an Active Suspension for an All-Terrain Tracked Vehicle - Illg, Igor; Tewes, Michael; Jäker, Karl-Peter; Trächtler, Ansgar (9th International Symposium on Advanced Vehicle Control (AVEC 2008))

Model-based Controller Design for the Paper Separation-Process in Automatic Teller Machines - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (The 9th International Conference on Motion and Vibration Control (Movic 2008))

Defining Plan Metrics for Multi-Agent Planning within Mechatronic Systems - Klöpper, Benjamin; Romaus, Christoph; Schmidt, Alexander; Voecking, Henner; Donoth, Jörg (ASME 2008 - International Design Engineering Technical Conferences & Computers and Information in Engineering Conference (IDETC/CIE))

The Active Guidance Module of a Rail-Bound Vehicle as an Application of Dependability Oriented Design in Self-Optimizing Systems - Sondermann-Wölke, Christoph; Müller, Thomas; Geisler, Jens; Trächtler, Ansgar; Böcker, Joachim (ASME 2008 - International Design Engineering Technical Conferences & Computers and Information in Engineering Conference (IDETC/CIE))

Multiobjective Optimization of Control Trajectories for the Guidance of a Rail-bound Vehicle - Geisler, Jens; Witting, Katrin; Trächtler, Ansgar; Dellnitz, Michael (Proc. 17th IFAC World Congress)

Tool Support for the Design of Self-Optimizing Mechatronic Multi-Agent Systems - Burmester, Sven; Giese, Holger; Münch, Eckehard; Oberschelp, Oliver; Klein, Florian; Scheideler, Peter (International Journal on Software Tools for Technology Transfer (STTT))

System Architecture and Risk Management for Autonomous Railway Convoys - Henke, Christian; Tichy, Matthias; Schneider, Tobias; Böcker, Joachim; Schäfer, Wilhelm (Proceedings of the 2nd Annual IEEE International Systems Conference, Montreal, Canada)

Improved Flexible Resource Management by Means of Look-Ahead Scheduling and Bayesian Forecasting - Oberthür, Simon; Znamenshchykov, Alex; Klöpper, Benjamin; Voecking, Henner (7th International Heinz Nixdorf Symposium: Self-optimizing Mechatronic Systems: Designing the Future)

Autonomes Kreuzungsmanagement für Kraftfahrzeuge - Trajektorienplanung mittels Dynamischer Programmierung - Bruns, Torsten; Trächtler, Ansgar (4. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren (AUTOREG 2008))

Self-Optimization of the Guidance Module of a Rail-bound Vehicle - Geisler, Jens; Witting, Katrin; Trächtler, Ansgar; Dellnitz, Michael (7th International Heinz Nixdorf Symposium: Self-optimizing Mechatronic Systems: Designing the Future)

Safe Online-Reconfiguration of Self-Optimizing Mechatronic Systems - Osmic, Semir; Münch, Eckehard; Trächtler, Ansgar; Henkler, Stefan; Schäfer, Wilhelm; Giese, Holger; Hirsch, Martin (7th International Heinz Nixdorf Symposium: Self-optimizing Mechatronic Systems: Designing the Future)

Modellbasierte Entwicklung eines volltragenden, vollaktiven Federungssystems für ein geländegängiges Nutzfahrzeug - Wielenberg, Andreas; Harchenko, Jewgenij; Jäker, Karl-Peter; Trächtler, Ansgar (4. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren (AUTOREG 2008))

A Multi-Agent Planning Problem for the Coordination of Function Modules - Klöpper, Benjamin; Romaus, Christoph; Schmidt, Alexander; Voecking, Henner (7th International Heinz Nixdorf Symposium: Self-optimizing Mechatronic Systems: Designing the Future)

FPGA-in-the-Loop Simulations with CAMEL-View - Münch, Eckehard; Gambuzza, Alfonso; Paiz, Carlos; Pohl, Christopher; Porrmann, Mario (In Proceedings of the 7th International Heinz Nixdorf Symposium)

Modellbildung, Analyse und Regelung eines aktiv gefederten Fahrzeugs - Schäfer, Erika; Jäker, Karl-Peter; Trächtler, Ansgar (4. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren (AUTOREG 2008))

Definition of Optimum Parameters of Elastic Support of the Electric Motor of a Drive of a Wheel for Improvement of Dynamics of the Wheel Machine - Poddubny, Wladimir; Trächtler, Ansgar; Jäker, Karl-Peter; Nachtigal, Vitalij (Мехатроника, Автоматизация, Управление (Mechatronik, Automatisierung, Regelung))

What Can We Gain from Transdisciplinary Visualization Courses? - Domik, Gitta; Chalmers, Alan; W. Fellner, Dieter; E. Rushmeier, Holly (Eurographics 2008 - Education Papers, Crete, Greece, April 14-18, 2008)

Learning English - the reading performance of a Japanese 'SUE' (successful user of English) - Rumlich, Dominik (Working papers in Applied Linguistics)

A simple pre-stress estimating method of langevin transducers - Bo, Fu; Ting, Li; Hemsel, Tobias (Piezoelectricity, Acoustic Waves, and Device Applications, 2008. SPAWDA 2008. Symposium on)
A simple pre-stress estimate method of Langevin transducers is studied. The measurement setup consists of a capacitor, an impedance converter and a voltmeter. Based on the piezoelectric equation and the basic circuit theory, the mathematical expression between the pre-stress and the voltage across the capacitor is derived. The pre-stress level can then be calculated out of the measurement of the capacitor voltage. In order to evaluate the precision of this method, a force washer is used to measure the pre-stress of the Langevin transducer. The result shows the pre-stress level obtained from this method is 30-40% higher than the pre-stress level measured by the force washer. This method is simple and can be used to estimate the pre-stress of various Langevin transducers. The precision of this method can be raised if d33 is identified under different pre-stress levels.
Keywords: capacitors; impedance convertors; piezoelectric transducers; stress analysis; Langevin transducers; basic circuit theory; capacitor; impedance converter; piezoelectric equation; pre-stress estimating method; voltmeter; Capacitors; Educational institutions; Equations; Force measurement; Impedance measurement; Manufacturing; Mechatronics; Piezoelectric transducers; Voltage; Voltmeters; Langevin transducer; capacitor; piezoelectric element; pre-stress

Local Ultrasonic Hyperthermia and Thermo-ablation: A Description and Theoretical Evaluation of Two Alternative Concepts for the Heat Therapy of Tumours - Lierke, Ernst-Günter; Hemsel, Tobias (Acta Acustica united with Acustica)
Ultrasonic hyperthermia and thermo-ablation are two promising alternatives for local overheating of deep-seated human tumours. After a short characterisation of the two techniques and the identification of the main parameters, results of an analytical theory of local heat up, cooling, and heat diffusion are presented. The theory is based on a spherical model for hyperthermia with a critical thermal dose and on a cylinder-symmetrical model for thermo-ablation with a critical temperature threshold for thermal toxicity and cell death through coagulative necrosis. Two representative hard ware concepts are discussed. The hyperthermia applicator consists of a MHz transducer, which rotates concentrically in a water filled capsule with acoustically transparent window, and radiates collimated or focussed ultrasound under 45$\,^{°}$ into a concentric target area of nearly spherical symmetry. The applicator for thermo-ablation is a MHz transducer which radiates high intensity focussed ultrasound (HIFU) into "cigar shaped" target areas at the focal zone. Typical therapy diagrams for both techniques are presented. They show therapeutic target volumes as functions of the therapy time with the peak temperature or the radiated acoustic power as parameters. These diagrams are discussed under consideration of power requirement, maximal sound intensity, and power efficiency at close to optimized frequency conditions.

Verlässlichkeitorientierte Technologiebewertung innovativer Aktortechnologien am Beispiel von Formgedächtnislegierungen - Müller, Thomas; Schiedeck, Florian; Hemsel, Tobias (2. Tagung des DVM -- Arbeitskreis Zuverlässigkeit mechatronischer und adaptronischer Systeme: Absicherung der Systemzuverlässigkeit, Koblenz)
EN: Although the use of new actuator technologies is quite enthusiastic, the realization of innovative systems based on these principles fails because of doubts in dependability. Until now, new working principles for actuators have not been systematically investigated in the means of dependability. Therefore we developed a proceeding for a dependability-oriented evaluation of technologies. This is shown in the case of shape memory alloy actuators. DE: Die Realisierung von Systemen mittels innovativer Aktortechnologien scheitert oftmals an der Skepsis gegenüber der Verlässlichkeit (Vertrauen in die zuverlässige und sichere Funktionalität der Technologie). Diese liegt darin begründet, dass neue Aktortechnologien bzw. die Integration von innovativen physikalischen Wirkprinzipen innerhalb neuer Aktorkonzepte bisher noch nicht systematisch im Kontext der Verlässlichkeit untersucht werden. Daher haben wir ein Vorgehen zur verlässlichkeitsorientierten Technologiebewertung entwickelt. Neben der detaillierten Darstellung des Vorgehensmodells wird es exemplarisch anhand von Formgedächtnislegierungen zur Entwicklung innovativer Antriebslösungen angewendet.
Keywords: EN: Dependability; Reliability; Evaluation of Technology; Actuators; Shape Memory Alloys DE: Verl{\

Driving concepts for bundled ultrasonic linear motors - Mracek, Maik; Hemsel, Tobias; Sattel, Thomas; Vasiljev, Piotr; Wallaschek, Jörg (Journal of Electroceramics)
Several positioning tasks demand translatory drive instead of rotary motion. To achieve drives that are capable, e.g., to drive the sunroof of a car or to lift a car's window, multiple miniaturized motors can be combined. But in this case many other questions arise: The electromechanical behavior of the individual motors differs slightly, the motor characteristics are strongly dependent on the driving parameters and the driven load, many applications need some extra power for special cases like overcoming higher forces periodically. Thus, the bundle of motors has to act well-organized and at last controlled to get an optimized drive that is not oversized and costly.
Keywords: Ultrasonic linear motor; High power; Control; Modeling; Characteristics

Service-Oriented Enterprise Architectures: Evolution of Concepts and Methods - Assmann, Martin; Engels, Gregor (Proc. of the 12th IEEE International Enterprise Distributed Object Computing Conference 2008 (EDOC 08), Munich (Germany))
This paper depicts the evolution of enterprise architectures to their today often used service-oriented form and presents a state-of-the-art development process for this kind of architecture. The development process covers both the development of business architecture as well as the appropriate software architecture. While showing up a possible form of further evolution of enterprise architectures, we identify the major challenges for future development methods of enterprise architectures.

Transition to Service-Oriented Enterprise Architecture - Assmann, Martin; Engels, Gregor (Proceedings of the Second European Conference on Software Architecture (ECSA 2008), Paphos (Cyprus))
Enterprise Architecture (EA) has undergone many changes since the IT has found its way into enterprises. At the moment the Service-Oriented Architecture (SOA) is being hyped but has also gained some importance. Implementing SOA can have many implications for an enterprise, depending on how visionary the implemented architecture is. This paper provides the description of an enterprise architecture that is fully-fledged concerning service-orientation and points out the architectural challenges that have to be mastered with future research results.

Comprehensive Architecture Evaluation and Management in Large Software-Systems - Salger, Frank; Bennicke, Marcel; Engels, Gregor; Lewerentz, Claus (Quality of Software Architectures. Models and Architectures)

Quasar Enterprise - Anwendungslandschaften serviceorientiert gestalten - Engels, Gregor; Voß, Markus (Software Engineering 2008. Fachtagung des GI-Fachbereichs Softwaretechnik)

Detecting and Resolving Process Model Differences in the Absence of a Change Log - Küster, Jochen; Gerth, Christian; Förster, Alexander; Engels, Gregor (Proceedings of the 6th International Conference on Business Process Management (BPM'08))
Business-driven development favors the construction of process models at different abstraction levels and by different people. As a consequence, there is a demand for consolidating different versions of process models by detecting and resolving differences. Existing approaches rely on the existence of a change log which logs the changes when changing a process model. However, in several scenarios such a change log does not exist and differences must be identified by comparing process models before and after changes have been made. In this paper, we present our approach to detecting and resolving differences between process models, in the absence of a change log. It is based on computing differences and deriving change operations for resolving differences, thereby providing a foundation for variant and version management in these cases.

A Method for Engineering a true Service-Oriented Architecture - Engels, Gregor; Hess, Andreas; Humm, Bernhard; Juwig, Oliver; Lohmann, Marc; Richter, Jan-Peter; Voß, Markus; Willkomm, Johannes (Proceedings of the Tenth International Conference on Enterprise Information Systems (ICEIS 2008), Barcelona (Spain))

Revised Use Case Point Method - Effort Estimation in Development Projects for Business Applications - Frohnhoff, Stephan; Engels, Gregor (Setting Quality Standards, Proceedings of the 11th International Conference on Quality Engineering in Software Technology (CONQUEST 2008), Potsdam (Germany))
Rapid and precise effort estimation of software development projects is crucial in IT industry. In a case study, the Use Case Point (UCP) method was applied to 15 commercial software development projects. The estimated efforts were compared with the incurred project efforts. We measured a standard deviation of 42 %. This is not acceptable for industrial usage. Therefore, we propose appropriate improvements of the Use Case Point method leading to significantly higher estimation accuracy with only 20 % standard deviation. The contribution of this paper is a detailed description of the improved Use Case Point method.

Qualitätssicherung im Business Process Modeling durch automatische Ableitung visueller Kontrakte aus heterogenen UML-Modellen - Mlynarski, Michael (Informatiktage 2008. Fachwissenschaftlicher Informatik-Kongress, 14. und 15. März 2008, B-IT Bonn-Aachen International Center for Information Technology in Bonn)

Combining Quality Assurance and Model Transformations in Business-Driven Development - Koehler, Jana; Gschwind, Thomas; Küster, Jochen; Pautasso, Cesare; Ryndina, Ksenia; Vanhatalo, Jussi; Völzer, Hagen (Proceedings of the 3rd International Symposium on Applications of Graph Transformations with Industrial Relevance 2007 (AGTIVE '07), Kassel (Germany))

Kontextsensitive Qualitätsplanung für Software-Modelle - Voigt, Hendrik; Engels, Gregor (Proceedings of Modellierung (2008), Berlin (Germany))
Der Goal Question Metric (GQM) Ansatz stellt eine allgemeine Qualitätsmanagementstrategie dar und berücksichtigt infolgedessen nicht die Besonderheiten von Software-Modellen. Wir haben eine kontextsensitive Qualitätsplanung für Software- Modelle entwickelt, die den GQM-Ansatz auf die Qualitätsplanung von Software- Modellen zuschneidet und um Konzepte und Aktivitäten erweitert. Dabei konzentrieren wir uns auf den Kontext eines Software-Modells als entscheidenden Einflussfaktor für die Dokumentation von Informationsbedürfnissen, Qualitätsverständnis und Messung. Unser Ansatz zur Qualitätsplanung besteht aus einem Metamodell zur Formulierung relevanter Inhalte und einem Prozess, der als Leitfaden bei der Planung dient.

Ein verfeinerter GQM-Ansatz zur Qualitätsbewertung von Software-Modellen - Voigt, Hendrik; Engels, Gregor (Proceedings of Software-Qualitätsmodellierung und -bewertung (SQMB '08), München, Germany)

Quality Plans for Measuring the Testability of Models - Voigt, Hendrik; Güldali, Baris; Engels, Gregor (Proceedings of the 11th International Conference on Quality Engineering in Software Technology (CONQUEST 2008), Potsdam (Germany))

A Quality Circle Tool for Software Models - Voigt, Hendrik; Ruhroth, Thomas (Proceedings of the 27th International Conference on Conceptual Modeling (ER 2008), Barcelona, Spain)

Predicting Coupling of Object-Centric Business Process Implementations - Wahler, Michael; Küster, Jochen (Proceedings of the 6th International Conference on Business Process Management)

Towards an Efficient Reuse of Test Cases for Software Product Lines - Wübbeke, Andreas (Proceedings of the 12th International Software Product Line Conference (SPLC 2008), Limerick (Ireland))

Network-Coding-Based Cooperative Transmission in Wireless Sensor Networks: Diversity-Multiplexing Tradeoff and Coverage Area Extension - H. Woldegebreal, Dereje; Karl, Holger (Wireless Sensor Networks, 5th European Conference, EWSN 2008, Bologna, Italy, January 30-February 1, 2008, Proceedings)

Integrating Multiuser Dynamic OFDMA into IEEE 802.11 WLANs - LLC/MAC Extensions and System Performance - Valentin, Stefan; Freitag, Thomas; Karl, Holger (Proceedings of IEEE International Conference on Communications, ICC 2008, Beijing, China, 19-23 May 2008)

Design and Evaluation of a Routing-Informed Cooperative MAC Protocol for Ad Hoc Networks - S. Lichte, Hermann; Valentin, Stefan; Karl, Holger; Aad, Imad; Loyola, Luis; Widmer, J{\ (INFOCOM 2008. 27th IEEE International Conference on Computer Communications, Joint Conference of the IEEE Computer and Communications Societies, 13-18 April 2008, Phoenix, AZ, USA)

Opportunistic relaying vs. selective cooperation: analyzing the occurrence-conditioned outage capacity - Valentin, Stefan; S. Lichte, Hermann; Karl, Holger; Aad, Imad; Loyola, Luis; Widmer, J. (Proceedings of the 11th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2008, Vancouver, British Columbia, Canada, October 27-31, 2008)

Decoding-based channel estimation for selective cooperation diversity protocols - Valentin, Stefan; Volkhausen, Tobias; Atay Onat, Furuzan; Yanikomeroglu, Halim; Karl, Holger (Proceedings of the IEEE 19th International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2008, 15-18 September 2008, Cannes, French Riviera, France)

Mobile Cooperative WLANs - MAC and Transceiver Design, Prototyping, and Field Measurements - Valentin, Stefan; S. Lichte, Hermann; Warneke, Daniel; Biermann, Thorsten; Funke, Rafael; Karl, Holger (Proceedings of the 68th IEEE Vehicular Technology Conference, VTC Fall 2008, 21-24 September 2008, Calgary, Alberta, Canada)

Incremental Network Coding in Cooperative Transmission Wireless Networks - H. Woldegebreal, Dereje; Valentin, Stefan; Karl, Holger (Proceedings of the 68th IEEE Vehicular Technology Conference, VTC Fall 2008, 21-24 September 2008, Calgary, Alberta, Canada)

Inaccuracies of input data relevant for PV yield prediction - Krauter, Stefan; Grunow, Paul; Preiss, A.; Rindert, S.; Ferretti, N. (Proceedings of the 33rd IEEE Photovoltaic Specialists Conference, San Diego (USA), 11.–16. Mai 2008, S. 2105–2109)

Wafer, Cell and Module Quality Requirements - Krauter, Stefan; Grunow, Paul (Photovoltaics International)